Effect of extraction on polyphenol content, antioxidant activity and pH in pegaga (centella asiatica) extract - Ong, Hooi Yung; Mohamad Yusof Maskat; Wan Aida Wan Mustapha (Universiti Kebangsaan Malaysia, 2010)
This study was carried out to determine the effect of temperature (50, 70 and 90 oC) and heating time (15, 30 and 90 minutes) during the extraction of pegaga and also to compare the effect of extraction using heat and non-heat methods. Parameters measured were total polyphenol content, antioxidant activity and pH. Results showed that with an increase in boiling temperature and time, total polyphenol content and antioxidant activity increased significantly except for extraction temperature of 90 oC for antioxidant activity. The total polyphenol content and antioxidant activity from samples prepared without heat treatment were significantly lower than extracts prepared using heat treatment. The pH of pegaga extract increased with increase in extraction temperature. However, pH of pegaga extract decreased with the increase in extraction time.